2012
DOI: 10.2478/s11536-012-0062-4
|View full text |Cite
|
Sign up to set email alerts
|

A study of antibiotic prescribing: the experience of Lithuanian and Russian GPs

Abstract: AbstractBackground. Globally, general practitioners (GPs) write more than 90% of all antibiotic prescriptions. This study examines the experiences of Lithuanian and Russian GPs in antibiotic prescription for upper respiratory tract infections, including their perceptions of when it is not indicated clinically or pharmacologically. Methods. 22 Lithuanian and 29 Russian GPs participated in five focus group discussions. Thematic analysis was used to analyse the data. Results. We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…The findings of this study indicate that a common policy in a primary care centre is a success factor in the task of improving prescribing habits. Corresponding results have been found in previous research as well as in a focus-group study on similar topics among Happy Audit participants in Lithuania and the Kaliningrad region [26,27]. …”
Section: Discussionsupporting
confidence: 88%
“…The findings of this study indicate that a common policy in a primary care centre is a success factor in the task of improving prescribing habits. Corresponding results have been found in previous research as well as in a focus-group study on similar topics among Happy Audit participants in Lithuania and the Kaliningrad region [26,27]. …”
Section: Discussionsupporting
confidence: 88%
“…This high level of patient trust in ABs has likewise been reported in other countries, and a study conducted in Russia and Lithuania found that prescribing ABs for URTI has become an integral and even common practice for these types of infections [6]. …”
Section: Discussionmentioning
confidence: 69%
“…Revealed non-pharmacological factors for antibiotic prescriptions that affect physician–patient communication about antibiotic prescription have been discussed elsewhere (37). …”
Section: Methodsmentioning
confidence: 99%